Pierre and His People: Tales of the Far North. Volume 3. - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pierre and His People: Tales of the Far North. Volume 3." by Gilbert Parker is a collection of narratives set in the rugged landscapes of the Canadian North, likely written during the late 19th century. The book presents a series of stories that revolve around the interactions of a diverse cast of characters, including Shon McGann, Pretty Pierre, and Jo Gordineer, as they navigate themes of adventure, camaraderie, and the challenges of life in the wilderness. At the start of the volume, readers are introduced to Shon McGann, who is singing nostalgically about his past adventures while surrounded by his companions in a mountain hut. The narrative unfolds with the banter among the characters as they discuss a toboggan ride and delve into a tale about the ghost of Guidon Mountain, showcasing the blend of folklore and personal histories that permeate their lives. Shon's character is established as a witty and charming figure, while the camaraderie among the group hints at deeper connections shaped by their shared experiences in the harsh yet beautiful northern landscape. This beginning promises readers an engaging exploration of adventure and friendship, setting the stage for the rich tapestry of stories to come. (This is an automatically generated summary.)
Shon McGann's tobogan ride -- Père Champagne -- The Scarlet Hunter -- The stone.
Release date is 2004-07-01
This eBook was produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian